ORGANIC CHEMISTRY IN DRUG DESIGN: A PATH TO SUSTAINABLE PHARMACEUTICALS - Rachel Chan; Lucas Wong; Nikhil Joshi (Yayasan Adra Karima Hubbi, 2025)
The pharmaceutical industry faces significant challenges related to sustainability, including the environmental impact of drug manufacturing and the need for more efficient drug discovery processes. Organic chemistry plays a vital role in addressing these challenges by providing innovative methodologies for drug design and development. This study aims to explore the integration of organic chemistry principles in the design of sustainable pharmaceuticals. The research focuses on identifying green chemistry approaches that can enhance the efficiency and reduce the ecological footprint of drug development. A comprehensive literature review was conducted to analyze recent advancements in organic chemistry related to drug design. Case studies of successful sustainable drug development projects were examined to illustrate the practical application of these principles. Laboratory experiments were also performed to evaluate the effectiveness of green synthetic methods. Findings indicate that the application of organic chemistry in drug design can significantly reduce waste and improve the efficiency of synthesis. Successful case studies demonstrated the feasibility of using environmentally friendly reagents and processes in drug development, leading to more sustainable pharmaceutical products. This research highlights the critical role of organic chemistry in promoting sustainable pharmaceuticals. By adopting green chemistry principles, the pharmaceutical industry can not only enhance its efficiency but also contribute positively to environmental sustainability, paving the way for a more responsible approach to drug development.